Letter - West, R.
1949-04-29 038-0008-001 Business Macaulay 4482 Tele. 3449. SALVINGDON, PILGRIMS' WAY, REIGATE, SURREY. 29/4/49 Dear Mr Tewson I believe Lady Layton wrote you some time ago with reference to the work of the National Joint Committee for Spanish Relief. This is to say that at its last meeting the Committee suggested that I should see you - if convenient to you - in regard to the possibility of establishing some link between the Trade Unions and the Adult Spaniards when the National Joint Committee lays down its work. Could you arrange to see me - any time during the hours of 9.30 & say 4 o/c at Transport House. I am in London every day except Sat. & Sundays. I will briefly explain 292/946/38/8(I)